Utility privatization and regulation a fair deal for consumers? - Ugaz, Cecilia; Waddams Price, Catherine; World Institute for Development Economics Research; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2003)
The authors address the question of infrastructure reforms in a novel way by focusing on the impact which they can have on consumers through the prices paid by different groups and on their access to the networks. They analyse original material from four Latin American countries - Argentina, Bolivia, Chile, Peru - and two European countries - Spain and the UK. Access is especially relevant when considering immature systems which have not yet extended to cover the majority of the population, as is the case in many Latin American countries. The authors also address the widespread impact of privatization on the economy (via macroeconomic influences) and the more general issues of subsidies and regulation which are endemic to these industries. The book focuses on the reform of four sectors: telecommunications, electricity, gas, and water and sanitation.
pt. I. Access, affordability and institutions -- pt. II. Country case studies.
"In association with UNU World Institute for Development Economics Reserach (UNU/WIDER)."
Includes bibliographical references and index.
Keywords: Public utilities -- Latin America; Poverty -- Latin America; Privatization -- Latin America; Electronic books